Governing Fairtrade: ethics of care and justice in the Argentinean wine industry. (24th March 2021) - Herman, Agatha
ABSTRACT: Globally, Fairtrade practices its ethic of trade justice and governs its multiple stakeholders through a universalising set of regulations. However, this essentialises what are, in reality, disparate, dynamic and contextual experiences. Engaging with Argentinean wine and wine grape producers, alongside European regulators, highlights the inherent tensions to this system with Fairtrade's global efforts being experienced as injustices at the producer level. This paper argues that overcoming the disconnect between 'justice-as-universal' and 'care-as-particular' is essential; combining these ethics will make Fairtrade's governance more responsive to the place-based realities of how it is actually experienced and lived. The institutionalisation of Fairtrade has precluded alternative ideas of thinking or doing trade justice and so more inclusive dialogues are needed to ensure all stakeholders can participate. Fairtrade needs to bridge its scales of operation through a decentralised governance structure to allow for fluid and direct discussions and actions over its rhetoric, practices and impacts. This is an important step towards actualising everyday care-full trade justice.